Litterfall and mineral return in two cork-oak forests in northeast spain - Caritat, A; Bertoni, G; Molinas, M; Oliva, M; Domínguez-Planella, A (Ann. For. Sci., 1996)
Seasonal trends in littertall and potential mineral return were studied in two cork-oak forest sites in the northeastern Iberian peninsula. The estimated average litter production was 3.9 Mg.ha-1.year -1 for one site and 4.6 Mg.ha-1.year-1 for the other; these figures are similar to those reported for holm-oak (Quercus ilex) forests in the same area. Seasonal litterfall patterns were typical of Mediterranean forest ecosystems. Leaves accounted for 46 to 78% of the total dry matter. Their annual weighted-average mineral composition was low in macronutrients (N 8-9; K 4-5; Mg 0.8-1.3; Ca 9-10 and P 0.4-1 mg.g-1) and relatively high in micronutrients such as Mn (2-2.2 mg.g-1) or Fe (0.3-0.4 mg.g-1). Minimum N and P concentrations were found during the growth period. Estimates of potential mineral return for an annual cycle were N 38-52, P 2.1-5.2, K 20-28, Ca 44-53 and Mg 5.4-5.0 kg.ha -1, depending on the site biomass and fertility.
Keywords: cork-oak; litterfall; Mediterranean forest ecosystems; nutrient cycling; Quercus suber